Bromelain from pineapple: A mini review of its industrial applications and future prospects - Thevika, Sarawanan; Rohaida, Che Man; Zatul Iffah, Mohd Arshad; Shalyda, Md Shaarani (Elsevier, 2025)
Bromelain, a proteolytic enzyme derived from the pineapple plant (Ananas comosus), has gained significant interest due to its diverse applications in food processing, medicine, cosmetics, and agriculture. Its enzymatic activity supports protein digestion, exhibits anti-inflammatory effects, aids in wound healing, and enhances seed priming. However, its industrial utilisation faces challenges, including compositional variability, stability concerns, and complex extraction and purification processes that result in low yields and high costs. Bromelain also competes with microbial proteases, which offer greater scalability and efficiency for large-scale production. Clinically, while generally safe, bromelain may cause adverse effects and interact with certain medications, with its long-term safety remaining uncertain. Despite these limitations, bromelain production presents a sustainable opportunity by repurposing agricultural waste from pineapple processing. Advances in biotechnology, including nanotechnology and optimised extraction techniques such as membrane filtration, reverse micellar systems, aqueous two-phase extraction, and chromatographic methods, continue to enhance its stability and potential applications. Future research should focus on overcoming these constraints to maximise bromelain's benefits across various industries.